Only his - Mallery, Susan (Mallery, Susan. Fool's gold, 2011)
"Wedding bells are ringing in Fool's Gold, but not for Nevada Hendrix. Her triplet sisters are engaged, and even her mother has a more active love life than she does. Determined to make a fresh start, she applies for her dream job, only to discover that her new boss is her first love. Maybe she could overlook the fact that they have seen each other naked, but she will never forget the way he broke her heart. Tucker Janack agrees to Nevada's "business only" ground rules. After all, love is a trap that the construction millionaire has avoided his whole life. But when great business partners turn out to be so much more, every rule gets broken. Will either of them be willing to try again, or will their past get in the way?" -- p. [4] of cover.